Light Ways with Poultry: Quick & Healthy Low-Fat Cooking from the Food Editors of Prevention Magazine (Prevention Magazine's Quick & Healthy Low-Fat Cooking) - Prevention Magazine Editors
The third volume in Prevention Magazine's Quick and Healthy Low-Fat Cooking Series includes make-ahead sauces and gravies, special cooking techniques, and delicious low-fat recipes, such as Chicken Paprikash and Sour Turkey Stir-Fry.